New Russian Translation of “The Life of Grigol Khandzteli” - Sophio Guliashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
The first editor of The Life of Grigol Khandzteli Nicholas Marr accompanied work with an entire volume of Russian translations along with researches and the diary about the journey in Tao-Klarjeti and Shavsheti. It was the start of the Giorgi Merchule’s story narrated in a foreign language. Very soon in 1917-1919 the Latin translation of the Life of Grigol Khandzteli was performed by Paul Peeters and in 1922-1923 along with other important Georgian works was published (Vie de St. Gregoire de Khandztha). Later, in 1956, „Lives and Legends of the Georgian Saints“ by David Marshall Lang with English translation of the Life of Grigol Khadzteli performed by Lang was published. (“The Life of St. Gregory of Khandzta”: Lives and Legends of the Georgian Saints, London 1956, pp. 155-65); in 2015 an American scholar of Norwegian origin Theophane-Erik Halvorson introduced a new English translation of The Life accompanied with the pictures captured in Nikozi. Before it in the December 1999 the 42nd edition of Russian journal Symbol located in Paris published new Russian translation of The Life of Grigol Khandzteli [9, pp. 245-341] made by Jozeph Zeteishvili. In 2008 Moscow publishing house CRITERIUM re-edited this masterpiece of Georgian Hagiog- raphy in the series named „mother of the Saints”. The present work is dedicated to the Russian translation made by Archpriest Ioseb Zeteishvili.